Numerical investigations on flow structure and heat transfer in a square duct equipped with double V-orifice - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2020)
Numerical predictions on heat transfer characteristic, flow topology and thermal performance assessment in a square duct are presented. The passive technique, insertion of the vortex generator, is opted to develop the heat transfer rate in the square duct heat exchanger. The vortex generator of the present research is Double V-Orifice (DVO). The square duct equipped with DVO is tested with various parameters. The influences of DVO height, b, to the duct height, H, or b/H, gap spacing between the outer edge of the orifice and the duct wall, s, to the duct height or s/H and flow directions (tip-pointing-Downstream and tip-pointing-Upstream) on flow pattern and heat transfer profile are considered for laminar flow regime with similar pitch, P, to duct height or P/H of 1. The Reynolds number, Re, based on the hydraulic diameter, Dh, of the square duct around 100 – 2000 is discussed. The numerical model is solved with the commercial software (finite volume method). As the numerical result, the square duct inserted with the DVO offers greater Nusselt number, Nu, than the plain duct around 1.00 – 14.80 times. The maximum thermal enhancement factor, TEF, for the square duct inserted with the DVO is found to be about 3.60 depended on s/H, b/H and flow direction. The flow and heat transfer profiles in the square duct inserted with the DVO are also illustrated.
Keywords: Double V-Orifice; Flow profile; Heat transfer; Numerical prediction; Square duct